2011
DOI: 10.1111/j.1526-4637.2011.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Compression Fracture Treatment with Vertebroplasty and Kyphoplasty: Experience in 407 Patients with 1,156 Fractures in a Tertiary Cancer Center

Abstract: Our single-center experience revealed that a large number of cancer patients suffer from painful VCFs. The use of VP or KP in treating painful VCFs in cancer patients has good efficacy and an acceptably low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…New fractures occurring after vertebroplasty may partly be due to the underlying disease, but some studies have reported a larger amount of new fractures next to the vertebrae treated with PMMA. [19][20][21] The maximum filling approach, in which as much cement as possible is injected into the vertebra, has been suggested to have a particularly detrimental effect. 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…New fractures occurring after vertebroplasty may partly be due to the underlying disease, but some studies have reported a larger amount of new fractures next to the vertebrae treated with PMMA. [19][20][21] The maximum filling approach, in which as much cement as possible is injected into the vertebra, has been suggested to have a particularly detrimental effect. 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…There is further evidence to support the safety and efficacy of percutaneous cement augmentation even in the setting of pathologic compression fractures [7][8][9][10][11]. In one large series of over 1150 treated fractures, these procedures provided significant relief from pain and related symptoms [8]. Serious complications occurred in less than 0.01% of cases.…”
Section: Management Of Vcfmentioning
confidence: 98%
“…There is a substantial body of evidence that supports the use of percutaneous cement augmentation, including vertebroplasty and balloon kyphoplasty, in the setting of osteoporotic compression fractures [6]. There is further evidence to support the safety and efficacy of percutaneous cement augmentation even in the setting of pathologic compression fractures [7][8][9][10][11]. In one large series of over 1150 treated fractures, these procedures provided significant relief from pain and related symptoms [8].…”
Section: Management Of Vcfmentioning
confidence: 99%
“…It must be taken into consideration here that the increase in vertebral body height by the Osseofix ® system is minor compared to that of kyphoplasty. Lin et al [30] found a significantly higher risk for vertebral refractures after vertebroplasty as a function of the increase in vertebral body height. The average Cobb angle (γ-angle) improved significantly from a preoperative angle of 12.3°to 10.8°after 12 months.…”
Section: Special Complicationsmentioning
confidence: 99%
“…The literature provides only sparse information about a secondary loss of height resulting in a certain recurrence of kyphosis [29]. Rates of 0 % to 63 % [30,31] for vertebroplasty and 14 -50 % for kyphoplasty are described [32,33] (follow-up period of 6 -27 months). Our rate of a secondary loss of height of 3.1 % is low.…”
Section: Special Complicationsmentioning
confidence: 99%